Optimalisasi Gulma Babadotan (Ageratum conyzoides) sebagai Pestisida Nabati pada Tanaman Cabai Rawit (Capsicum frutescens L.) - Herlin, Weri; Fatkha, Farah Nabila; Zagar, Zagar; Destia, Heni; Yuniva, Ester Akta (Seminar Nasional Lahan Suboptimal, 2024)
Herlin, W., Fatkha, F. N., Zagar, Z., Destia, H., & Yuniva, E. A. (2024). Optimization of Babadotan weed (Ageratum conyzoides) as a vegetable pesticide on cayenne pepper plants (Capsicum frutescens L.) . In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-12 Tahun 2024, Palembang  21 Oktober 2024. (pp. 195–201).  Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).Chili pepper plants (Capsicum frutescens L.) have high potential for cultivation. The density of pests that attack cultivated plants causes the pest population to swell. This study aimed to determine the effectiveness of babadotan weeds as botanical pesticides on chili pepper plants. The method used in this study was a Randomized Block Design (RAK), using 5 treatments, namely P0 (control), P1 (50 g / L), P2 (100 g / L), P3 (150 g / L), P4 (200 g / L) consisting of 6 replications with a total of 30 plants. The results of this study showed the growth of chili plants that were given botanical pesticides from several treatments carried out, namely plants that were not treated or not given pesticides were attacked more than chili plants that were given a lot of pesticides. In terms of plant height, the growth of chili plants that were given more botanical pesticides was higher than plants that were given less pesticides, in terms of the number of leaves, chili plants that were given more botanical pesticides had more leaves than chili plants that received less treatment. The conclusion of this study shows that botanical pesticides from babadotan weeds act as insecticides, repellents, binders, and pest growth inhibitors. Thus, it is necessary to use insecticides in the right dosage to control pest attacks on cayenne pepper.